Considerations on competency-based training and the One Health approach (FAVE Sección Ciencias Veterinarias, 2021)
The One health approach requires a close relationship between veterinary professionals and other actors and factors in the environment where they carry out their activities. This paper addresses the aspects that should be considered when including the domains of the One Health approach competencies in the context of a veterinary study program. Features of the curricular designs are discussed and positions on competency-based training are analyzed in order to propose the option of the complex-systemic model. In order for veterinarians to be able to enhance their effective performance and positively impact on their working environments, it is necessary to strengthen their systemic thinking about the interdependence of human, animal and environmental health, as well as their ability to move in different social, political, legal and cultural environments. Veterinary medicine professionals must be competent to design, manage and evaluate interactions between humans, animals and their environment and to be part of multidisciplinary teams. Educational strategies to enhance students' understanding of the sociological and ecological determinants of health, as well as their professional responsibilities, should not be an add-on to too fragmented and disciplinary curricula.
Keywords: Competences; Curricular design; Teaching strategy; One Health